Konsumsi makanan jajanan berpengaruh terhadap obesitas sentral pada mahasiswa berbasis pesantren - Lulu' Luthfiya; Hafidhotun Nabawiyah (ARGIPA (Arsip Gizi dan Pangan), 2022)
The prevalence of central obesity at the age above 15 years was 31%. Adolescent girls are a group at risk for central obesity. One of the factors that influence the incidence of central obesity is the pattern of snack food consumption. This study aimed to determine the relationship between the pattern of snack food consumption including frequency, energy, and fat intake on central obesity. The study design was case control, using the OR statistical test with a 95% confidence level. The research sample was taken by purposive sampling in each group of 36 subjects, calculated using the hypothesis test for an odd ratio formula. Dietary data were obtained through interviewing using the SQ FFQ questionnaire. Central obesity data obtained by measuring the circumference of the abdomen. Data analysis used chi square test. The results of the analysis showed that there was a relationship between the frequency of snack food consumption (p = 0.013 ; OR = 6.15), energy intake of snacks (p = 0.017; OR = 5.63) and fat intake of snacks (p = 0.001; OR = 10.9) against central obesity. It could be concluded that snack food consumption pattern has an effect on central obesity.